Alveolar ridge dimensional changes following ridge preservation procedure with novel devices: part 3 – histological analysis in non‐human primate model. Issue 11 (19th April 2017) - Su, Yingying; Tang, Jianxia; Min, Seiko; Guo, Lijia; Liu, Yitong; Xie, Yilin; Xiong, Jimin; Wang, Songlin; Araújo, Mauricio G.; Zadeh, Homayoun H.; Liu, Yi
Abstract: Objectives: This study sought to investigate the histological changes following tooth extraction, ridge preservation and augmentation, using novel devices designed to obturate the oral orifice of extraction sockets (SocketKAP™) and provide structural support for sockets with defective bony walls (SocketKAGE™) in a non‐human primate model. Material and methods: Six Macaca fascicularis were imaged by cone beam computed tomography to register their preoperative alveolar bone. Three teeth were extracted in each animal, yielding intact socket walls and were divided into three intervention groups: unassisted healing negative control (Group A); SocketKAP™ (Group B); filled with anorganic bovine bone mineral (ABBM) + SocketKAP™ (Group C). Three additional teeth were extracted in each animal, followed by surgical resection of the entire buccal alveolar bone and divided into three groups: negative control (Group D); SocketKAP™ + SocketKAGE™ (Group E); ABBM + SocketKAP™ + SocketKAGE™ (Group F). Animals were euthanized after 12 weeks, and treatment sites were examined by histology and histomorphometric analysis. Results: Control sockets with unassisted healing (Groups A and D) underwent severe loss of bone width, height and total area (approximately 40–60% loss). Application of SocketKAP™ in sites with intact walls, as well as SocketKAP™ plus SocketKAGE™ in sites with defective buccal walls lead to higher preservation of alveolar bone height after 12 weeks post‐intervention. Addition of ABBM leads to the highest degree of alveolar bone dimensional preservation. Control sites with unassisted healing (Groups A and D), as well as sites treated with extraction socket devices (Groups B and E) without ABBM yielded higher percentage of vital bone, compared with sites filled with ABBM (Groups C and F). No adverse histological responses were noted to SocketKAP™ or SocketKAGE™ devices. Conclusions: SocketKAP™ + SocketKAGE™ devices proved effective in reducing post‐extraction alveolar bone resorption mediating favorable wound healing within sockets. Addition of ABBM was associated with reduced volumetric loss, although the bone fill was characterized by less mature as well as more woven bone.